In 2005, J. Sondow found a surprising formula for the Euler-Mascheroni constant $ \gamma $. The formula is $$ \gamma = \int_{0}^{1} \int_{0}^{1} \frac{x - 1}{(1 - x y) \log(x y)} ~ \mathrm{d}{x} ~ \mathrm{d}{y}. $$ Now, the definition of $ \gamma $ is $$ \gamma \stackrel{\text{def}}{=} \lim_{n \to \infty} \left[ \sum_{k = 1}^{n} \frac{1}{k} - \log(n) \right]. $$ I have tried using the geometric series $$ \frac{1}{1 - x y} = \sum_{n = 0}^{\infty} x^{n} y^{n} $$ to obtain a proof, but it would not work. Thanks for any help.


Here is an approach that reduces to a single integral:

Notice that:

$$\int_{0}^{1}\frac{x}{(1-xy)\ln(xy)}dy=\int_{0}^{x}\frac{1}{(1-xy)\ln(xy)}d(xy)=\int_{0}^{x}\frac{1}{(1-t)\ln t}dt......(1)$$

So $$I =\int_{0}^{1}\int_{0}^{1}\frac{x-1}{(1-xy)\ln(xy)}dxdy=\lim_{\epsilon \rightarrow 0}\int_{0}^{1-\epsilon}\frac{x-1}{x}\left[\int_{0}^{x}\frac{1}{(1-t)\ln t}dt\right]dx.$$

Integrating by parts,

$$I =\lim_{\epsilon \rightarrow 0}\left[(x-\ln x)\int_{0}^{x}\frac{1}{(1-t)\ln t}dt\Big|_{0}^{1-\epsilon}-\int_{0}^{1-\epsilon}\frac{x-\ln x}{(1-x)\ln x}dx\right]= \\ \lim_{\epsilon \rightarrow 0}\left[[1-\epsilon-\ln(1-\epsilon)]\int_{0}^{1-\epsilon}\frac{1}{(1-x)\ln x}dx-\int_{0}^{1-\epsilon}\frac{x-\ln x}{(1-x)\ln x}dx\right]= \\\lim_{\epsilon \rightarrow 0}\left[-[\epsilon+\ln(1-\epsilon)]\int_{0}^{1-\epsilon}\frac{1}{(1-x)\ln x}dx+\int_{0}^{1-\epsilon}\left[\frac1{1-x}+\frac1{\ln x}\right]dx\right]=\int_{0}^{1}\left[\frac1{1-x}+\frac1{\ln x}\right]dx = \gamma,$$

where the last single-integral representation of $\gamma$ is well known.

  • $\begingroup$ A very clever solution! $\endgroup$ – Berrick Caleb Fillmore Jun 22 '14 at 23:46
  • $\begingroup$ Thank you very much. It took me a while to understand the transformation of the double integral in simple integral. The remaining solution is routine. $\endgroup$ – Mathsource Jun 22 '14 at 23:49
  • 3
    $\begingroup$ I think your technique will serve to show that $\int_{0}^{1}\int_{0}^{1}\frac{x - 1}{(1 + xy)\log(xy)}dxdy = \log(\frac{4}{\pi})$. $\endgroup$ – Mathsource Jun 22 '14 at 23:54
  • $\begingroup$ @Berrick Fillmore: Thanks $\endgroup$ – RRL Jun 22 '14 at 23:55
  • $\begingroup$ @MathFacts: As an improper integral we should set lower limit to $\delta$ and take limit as $\delta \rightarrow 0$. The lower boundary term should vanish. $\endgroup$ – RRL Jun 22 '14 at 23:57

This$\require{autoload-all}$ post outlines exactly how you would use the geometric series to reach the series that the original post has given. The beauty of this method lies in it's generalizations which I have placed several examples of in my post. If you want to see an easier method of finding the answer to the specific integral, see my other answer.

I will begin by first defining the exponential integral and then proving some lemmas which will assist in the proof. We write ${\operatorname{Ei}(x)}$ for the exponential integral and it is defined as follows.

$$\operatorname{Ei}(x) = -\int_{-x}^\infty \frac{e^{-t}}{t}\,\mathrm{d}t$$

I will use the following properties (hover over each statement for reasoning):

$$\mathtip{\lim_{x\to -\infty} \operatorname{Ei}(x) = 0}{\text{Clear from the definition of } \operatorname{Ei}(x).} \tag{1a}$$

$$\mathtip{\frac{\mathrm{d}}{\mathrm{d}x} \operatorname{Ei}(x) = \frac{e^x}{x}}{\text{Clear from the definition of } \operatorname{Ei}(x).} \tag{1b}$$

$$\mathtip{\int\operatorname{Ei}(x)\, \mathrm{d}x = x\operatorname{Ei}(x) – e^x + C}{\text{Integrate by parts or take the derivative of the right hand side.}{}} \tag{1c}$$

$$\mathtip{\int \operatorname{Ei}(x)e^{\alpha x}\, \mathrm{d}x = \frac{e^{\alpha x}\operatorname{Ei}(x) -\operatorname{Ei}((\alpha+1)x)}{\alpha} + C}{\text{Integrate by parts or take the derivative of the right hand side.}{}} \tag{1d}$$

I will begin with two preliminary lemmas.

Lemma $1$:

$$\int_0^1 \frac{x^n}{\log(ax)} \mathrm{d}x = a^{-n-1}\operatorname{Ei}((n+1)\log(a)) \tag{2}$$

$$ \toggle{ \enclose{roundedbox}{\text{ Click to Reveal Proof }} }{ \boxed{\text{Substitute } -\log(ax) = u}\\[.2cm] \int_{\infty}^{-\log(a)}-\frac{(e^u/a)^{n+1}}{u} \mathrm{d}u\\[.2cm] \boxed{\text{Simplify and use properties of integration}}\\[.2cm] \int_{-\log(a)}^{\infty}a^{-n-1}\frac{e^{(n+1)u}}{u} \mathrm{d}u\\[.2cm] \boxed{\text{Substitute }t = (n+1)u\text{ and then evaluate using the definition of }\operatorname{Ei}(x).}\\[.2cm] \int_0^1 \frac{x^n}{\log(ax)} \mathrm{d}x = a^{-n-1}\operatorname{Ei}((n+1)\log(a))\\ \enclose{roundedbox}{\text{ Click to Close Proof}}}\endtoggle $$

Lemma $2 $ (very significant):

$$\int_0^1 \dfrac{\operatorname{Ei}(a\log(y))}{y^n} \mathrm{d}y = \lim_{n_0\to n} \frac{1}{n_0-1}\log\left(1+\frac{1-n_0}{a}\right) \tag{3}$$

Proof is located at the bottom of the post. The limit must be used for the case $n = 1$.

Now to evaluate the integral:

$$ \begin{align} I &= \int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{x-1}{(1 – xy)\log(xy)}\mathrm{d}x\mathrm{d}y \\ &= \lim_{n\to\infty}\int_{0}^{1}\!\!\int_{0}^{1}\!\sum_{k=0}^n \left[\frac{x^{k+1}y^k}{\log(xy)} - \frac{x^{k}y^k}{\log(xy)}\right]\mathrm{d}x\mathrm{d}y \end{align}$$

Using $(2)$:

$$I = \lim_{n\to\infty}\int_{0}^{1} \sum_{k=0}^\infty \left[\frac{\operatorname{Ei}((k+2)\log(y))}{y^2}- \frac{\operatorname{Ei}((k+1)\log(y))}{y}\right] \mathrm{d}y$$

Using $(3)$:

$$I = \lim_{n\to\infty}\sum_{k=0}^n \left[\log\left(1-\frac{1}{k+2}\right)+\frac{1}{k+1}\right]$$


$$\begin{align}I &= \lim_{n\to\infty} \sum_{k=1}^n \left[\log\left(\frac{k}{k+1}\right)+\frac{1}{k}\right]\\ &= \lim_{n\to\infty}\sum_{k=1}^n \left[\log(k)-\log(k+1)+\frac{1}{k}\right]\\ &= \lim_{n\to\infty}\sum_{k=1}^{\infty}\frac{1}{k} - \log(n)\end{align}$$

$\LARGE \text{Generalizations:}$

This approach is not very good for the simple integral given in the original post but it is a very strong approach in general. In the proof of Lemma 2, we were able to develop a general formula for $I_n$. Using the same technique, it is possible to evaluate more complicated integrals such as

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{(x-1)^2}{(1 – xy)\log(xy)}\mathrm{d}x\mathrm{d}y = \log(\sqrt{2}) - \gamma$$

In fact, if we let $P(x)$ be any polynomial, we can find a closed form for

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{(x-1)P(x)}{(1 – xy)\log(xy)}\mathrm{d}x\mathrm{d}y$$

The factor of $(x-1)$ exists to ensure the numerator goes to zero as $x \to 1$. In general, we can do more than just polynomials in $x$. Here are some of the more interesting results that can be obtained

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{\sqrt{x}(x-1)}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y = \frac{1}{3} (\log (36)-2 \log (\pi ))$$

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{x^3+9x^2-11x+1}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y =\log(16)+\frac{\log(3)}{3}+\frac{5\log(2)}{6} - \gamma\\$$

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{\sqrt[4]{y}\sqrt{x}(1-x)}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y =\frac{4}{5} \!\left(\log (24)-2 \log (\pi )+4 \log \left(\Gamma (5/4)\right)\right)$$

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{y^{\pi}(x-1)}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y = \frac{\log (\pi )+\log \left(\left(-6+11 \pi -6 \pi ^2+\pi ^3\right) \Gamma (-3+\pi )\right)}{(\pi -1) \pi }$$

$$\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{x^{\pi}(x-1)}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y = -\frac{\log (\pi -3)-\pi \log (1+\pi )+\log \left(\pi \left(2-3 \pi +\pi ^2\right) \Gamma (-3+\pi )\right)}{\pi (1+\pi )}$$

The most significant one (in my opinion) is this one:

$$\boxed{\displaystyle\int_{0}^{1}\!\!\int_{0}^{1}\!\dfrac{x^{n}y^{n}(x-1)}{(1 – xy)\log(xy)}\,\mathrm{d}x\mathrm{d}y = \log(1+n)-\psi(1+n)}$$

This is not only a beautiful formula but it allows us to say that the integral of the original question can be easily shown to be $-\psi(1) = \gamma$. In this case, $\psi$ is the polygamma function. See my other answer for a quick route to developing this formula.

Here is the proof of Lemma 2. If you don't understand a step, hover over the equations. Note that $a+1>n$. The final generalization of $I_n$ is very useful for the generalization I later prove.

$$\begin{align}I_n &= \int_0^1 \frac{\operatorname{Ei}(a \log (y))}{y^n} \mathrm{d}y\\[.3cm] &\mathtip{= \int_{-\infty}^{0}\frac{\operatorname{Ei}(u)}{e^{n\cdot u/a}}\frac{e^{u/a}}{a} \mathrm{d}u}{\text{Substitute } u = a\log(y). \text{ and then integrate using property (1d)}}\\[.3cm] &\mathtip{= \left. \frac{e^{(1-n)u/a}\operatorname{Ei}(u)-\operatorname{Ei}((a+1-n)u/a)}{1-n} \right|_{-\infty}^{\,0}}{\text{Integrate using property (1d)}.}\\[.2cm] &\mathtip{=\left. \frac{y^{1-n}\operatorname{Ei}(a\log(y))-\operatorname{Ei}((a+1-n)\log(y))}{1-n} \right|_{\,0}^{\,1}}{\text{Substitute back in for }y.} \end{align}$$ To show that $I_1 = -1/a$ simply take the limit as $n \to 1$ using L'Hopital's rule and then evaluate. To find $I_n$ for $n > 1$ consider the following limits.

$$\begin{align} \text{Lower Limit} &= \lim_{y\to 0}\frac{y^{1-n}\operatorname{Ei}(a\log(y))-\operatorname{Ei}((a+1-n)\log(y))}{1-n} \\[.3cm] &\mathtip{=\lim_{y\to 0}\frac{\operatorname{Ei}(a\log(y))-y^{n-1}\operatorname{Ei}((a+1-n)\log(y))}{(1-n)y^{1-n}}}{\text{Re-arrange terms}.} \\[.3cm] &\mathtip{\!\overset{\rm{L'H}}{=} \lim_{y\to 0}-\frac{\operatorname{Ei}((a+1-n)\log(y))}{(1-n)}}{\text{Apply L'Hopitals rule using (1b)}.}\\[.3cm] &\mathtip{= 0.}{\text{Evaluate using (1d)}.} \end{align}$$

$$\text{Upper Limit} = \lim_{y\to 1}\frac{y^{1-n}\operatorname{Ei}(a\log(y))-\operatorname{Ei}((a+1-n)\log(y))}{1-n}$$

The upper limit is trivial with a simple Taylor series expansion. The upper limit is equal to $$\dfrac{\log(a) - \log(a+1-n)}{1-n}$$ With this,

$$\begin{align}I_n &= \frac{1}{n-1}\log\left(1+\frac{1-n}{a}\right) \\ I_1 &= -\frac{1}{a} \\ I_2 &= \log\left(1-\frac{1}{a}\right)\end{align}$$

This completes the proof of lemma 2.

It is worth noting that $I_1$ can be computed by taking the limit of $I_n$ as $n \to 1$. Furthermore, the above analysis did not depend on $n$ being an integer or being positive. This means that we can write for any $n \in \mathbb{R}$

$$I_n = \lim_{n_0\to n} \frac{1}{n_0-1}\log\left(1+\frac{1-n_0}{a}\right)$$

  • 1
    $\begingroup$ Also I like your solution. Contributes significantly in this matter. $\endgroup$ – Mathsource Jun 23 '14 at 3:03

I feel like I must submit another answer to this question as I have found a much simpler solution.

Let $$I'(n) = \int_0^1\!\!\int_0^1 \frac{x^ny^n(x-1)}{1-xy} \,\mathrm{d}x\mathrm{d}y$$

Using the geometric series, integrating, and then using partial fractions

$$\begin{align}I'(n) &= \lim_{N\to\infty}\sum_{k=0}^{N}-\frac{1}{(k+n)(1+k+n)^2}\\ &= \lim_{N\to\infty}\sum_{k=0}^{N} \frac{1}{k+n+1}-\frac{1}{k+n} + \sum_{k=0}^{N} \frac{1}{(k+n+1)^2} \end{align}$$

The first sum telescopes and the second one can be evaluated using the polygamma function. We have that

$$\psi^{(n)}(z) = \frac{\mathrm d^{n+1}}{\mathrm dz^{n+1}}\log \Gamma(z)= (-1)^{n+1}n! \sum_{k=0}^{\infty} \frac{1}{(z+k)^{n+1}}$$

Use this to find and expression for $I'(n)$ and then integrate with respect to $n$.

$$I'(n) =\int_0^1\!\!\int_0^1 \frac{x^ny^n(x-1)}{1-xy} \,\mathrm{d}x\mathrm{d}y = \frac{1}{n+1} - \psi^{(1)}(n+1) $$

$$I(n) = \int_0^1\!\!\int_0^1 \frac{x^ny^n(x-1)}{(1-xy)\log(xy)} \,\mathrm{d}x\mathrm{d}y = \log(n+1) - \psi(n+1) $$

$$\boxed{\displaystyle I(0) = \int_0^1\!\!\int_0^1 \frac{x-1}{(1-xy)\log(xy)} \,\mathrm{d}x\mathrm{d}y = - \psi(1) = \gamma}$$


$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} &\bbox[10px,#ffd]{\ds{\int_{0}^{1}\int_{0}^{1}{x - 1 \over \pars{1 - xy} \ln\pars{xy}}\,\dd x\,\dd y}} = \int_{0}^{1}{1 \over y^{2}}\int_{0}^{1}{xy - y \over \pars{1 - xy} \ln\pars{xy}}\,y\,\dd x\,\dd y \\[5mm] = &\ \int_{0}^{1}{1 \over y^{2}}\int_{0}^{y}{x - y \over \pars{1 - x} \ln\pars{x}}\,\dd x\,\dd y = \int_{0}^{1}{1 \over \pars{1 - x} \ln\pars{x}}\int_{x}^{1}{x - y \over y^{2}}\,\dd y\,\dd x \\[5mm] = &\ \int_{0}^{1}{1 \over \pars{1 - x} \ln\pars{x}}\bracks{1 - x + \ln\pars{x}}\dd x = \int_{0}^{1}{1 - x + \ln\pars{x} \over 1 - x} \overbrace{\bracks{-\int_{0}^{\infty}x^{t}\,\dd t}} ^{\ds{1 \over \ln\pars{x}}}\ \dd x \\[5mm] = &\ \int_{0}^{\infty}\int_{0}^{1}{x^{t + 1} - x^{t} - x^{t}\ln\pars{x} \over 1 - x} \,\dd x\,\dd t\label{1}\tag{1} \end{align}

\begin{align} &\bbox[10px,#ffd]{\ds{% \int_{0}^{1}{x^{t + 1} - x^{t} - x^{t}\ln\pars{x} \over 1 - x}\,\dd x}} = \left.\partiald{}{\mu}\int_{0}^{1}{x^{t + 1}\mu - x^{t}\mu - x^{t}\pars{x^{\mu} - 1} \over 1 - x}\,\dd x\,\right\vert_{\ \mu\ =\ 0} \\[5mm] = &\ \partiald{}{\mu}\bracks{% \mu\int_{0}^{1}{1 - x^{t} \over 1 - x}\,\dd x - \mu\int_{0}^{1}{1 - x^{t + 1} \over 1 - x}\,\dd x + \int_{0}^{1}{1 - x^{t + \mu} \over 1 - x}\,\dd x - \int_{0}^{1}{1 - x^{t} \over 1 - x}\,\dd x}_{\ \mu\ =\ 0} \\[5mm] = &\ \Psi\pars{t + 1} - \Psi\pars{t + 2} + \Psi\, '\pars{t + 1} = -\,{1 \over t + 1} + \Psi\,'\pars{t + 1}\label{2}\tag{2} \end{align}

where $\ds{\Psi}$ is the Digamma Function. With \eqref{1} and \eqref{2}:

\begin{align} &\bbox[10px,#ffd]{\ds{\int_{0}^{1}\int_{0}^{1}{x - 1 \over \pars{1 - xy} \ln\pars{xy}}\,\dd x\,\dd y}} = \lim_{R \to \infty}\int_{0}^{R} \bracks{-\,{1 \over t + 1} + \Psi\,'\pars{t + 1}}\dd t \\[5mm] = &\ \lim_{R \to \infty}\bracks{-\ln\pars{R + 1} + \Psi\pars{R + 1} - \Psi\pars{1}} = \bbx{\gamma} \end{align}

Note that $\ds{\Psi\pars{1} = -\gamma}$ and $\ds{\Psi\pars{z} \sim \ln\pars{z} - {1 \over 2z} - {1 \over 12z^{2}}}$ as $\ds{\verts{z} \to\ \infty}$ with $\ds{\verts{\arg{z}} < \pi}$.
See A & S Table.


We want use the transformation formula. \begin{align*} &U:= \left\lbrace (t,r) \mid t \in (0,1), r \in (t,1) \right\rbrace , V:= (0,1)^2, \\ &f: V \rightarrow \mathbb{R}, \left( \begin{array}{r} x\\ y\\ \end{array} \right) \mapsto \frac{x - 1}{(1-xy) \cdot ln(xy)}, \\ &\varphi: U \rightarrow V, \left( \begin{array}{r} t\\ r\\ \end{array}\right) \mapsto \left( \begin{array}{r} t/r\\ r\\ \end{array} \right), \end{align*}

\begin{align*} \varphi ^{-1}: V \rightarrow U, \left( \begin{array}{r} t\\ r\\ \end{array}\right) \mapsto \left( \begin{array}{r} t \cdot r\\ r\\ \end{array} \right) \end{align*}

\begin{align*} D\varphi = \left( \begin{array}{rr} 1/r & -t/r^2\\ 0 & 1\\ \end{array}\right), Det(D\varphi) = \frac{1}{r}. \end{align*}

So we can use the transformation.

\begin{align*} \int_0^1 \int_0^1 \frac{x-1}{(1-xy)\cdot ln(xy)} dx \, dy &= \int_0^1 \int_t^1 \frac{(t/r) - 1}{(1-t) \cdot ln(t)} \cdot \frac{1}{r} \, dr \, dt \\ &= \int_0^1 \int_t^1 \left( \frac{t}{(1-t) \cdot ln(t)} \cdot \frac{1}{r^2} - \frac{1}{r} \cdot \frac{1}{(1-t) \cdot ln(t)} \right) \, dr \, dt \\ &= \int_0^1 \left[ -\frac{1}{r} \cdot \frac{t}{(1-t) \cdot ln(t)} - \frac{ln(r)}{(1-t)\cdot ln(t)} \right]_t^1 \, dt \\ &= \int_0^1 \left( \frac{1-t}{(1-t)\cdot ln(t)} + \frac{ln(t)}{(1-t) \cdot ln(t)} \right) \, dt \\ &= \int_0^1 \left( \frac{1}{ln(t)} + \frac{1}{1-t} \right) \, dt \end{align*}

The last integral represented $\gamma$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.